DC/DC converter control using suggested artificial intelligent controllers - Issa Ahmed Abed; Samar Hameed Majeed (IAES International Journal of Artificial Intelligence (IJ-AI), 2021)
In order to provide constant DC voltage, buck converter is used which is a common converter in different applications. The use of artificial control methods for DC/DC converter will increase the productivity, spend low energy, and able to avoid the changes. Here, in order to control the proposed converter, intelligent regulation is utilized. Different methods have been suggested to satisfy the need of the output. The work uses proportional-integral-derivative (PID) controller which is received the error difference between the output and the desired. Fuzzy logic controller (FLC) is also used. While the fuzzy-PID supervised (FSC-PID) where the parameters of the PID is updated using the fuzzy system. The explanation of the proposed controllers is presented in this paper. PID, fuzzy logic controller, and fuzzy-PID supervised have been designed and implemented using MATLAB in order to settle the output of buck DC/DC converter. The complete system has been built in MATLAB/Simulink. The proposed controller keeps track the output to be exactly the set signal.